PERBANDINGAN SISTEM EKONOMI DAN CIRI UTAMA EKONOMI SYARIAH - Maryam Batubara; Assyfa Urrahman; Dea Rahma Novita; Hafizah Mahira Nasution; Rizky Aulia Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Each country has a different economic system. The system adopted by a country is usually in accordance with that country's ideology. For example, a system based on Islamic sharia, namely the Islamic economic system. Those who adhere to this system are Islamic countries in the world, but several countries, especially Indonesia, have implemented an Islamic economic system with the presence of several banks labeled sharia. The economic system is a combination of two words consisting of